1997
DOI: 10.1128/aem.63.10.3972-3977.1997
|View full text |Cite
|
Sign up to set email alerts
|

Induced Natural Transformation of Acinetobacter calcoaceticus in Soil Microcosms

Abstract: Factors affecting natural transformation of Acinetobacter calcoaceticus BD413 with homologous chromosomal DNA in a silt loam soil microcosm were investigated. Inducible transformation of declining populations of noncompetent A. calcoaceticus cells was detectable for up to 6 days when a simple carbon source, salts, and freshly added DNA were used. In two different experimental setups, the residence time in soil of induced cells could be increased to either 11 or 24 h before DNA addition without reduced transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…And, indeed, development of competence in a soil residing bacterium @. calcoaceticus) was recently shown for the first time in soil (Nielsen et al, 1997~).…”
Section: Transformability Of Bacteria In Natural Environmentsmentioning
confidence: 92%
“…And, indeed, development of competence in a soil residing bacterium @. calcoaceticus) was recently shown for the first time in soil (Nielsen et al, 1997~).…”
Section: Transformability Of Bacteria In Natural Environmentsmentioning
confidence: 92%
“…Transfer frequency of antibiotic resistance is increased in fertilizer-amended soil Sludge, MSW-compost and manure may be regarded 'hot spots' for HGT due to the high number of bacteria and high nutrient levels. A laboratory experiment has shown increased frequency of transfer of heavy metal resistance genes due to nutrient amendment (Top et al, 1990), and in another study, natural transformation of Acinetobacter calcoaceticus was induced by nutrients, carbon and salts (Nielsen et al, 1997). Finally, manure has been shown to promote the horizontal transfer of antibiotic resistance genes in soil due to high loads of broad-host-range plasmids (Smalla et al, 2000).…”
Section: Co-selection Of Mercury and Antibiotic Resistancementioning
confidence: 99%
“…Based on these in vitro studies described earlier, it is difficult to determine the environmental signals that could trigger competence in Acinetobacter. Nielsen et al (1997) performed soil microcosm studies ('in situ') and observed the induction of competence by nutrient upshifts, as well as a transformation-enhancing effect of phosphate. These authors concluded that 'poorly transformable A. calcoaceticus cells can be induced to undergo natural transformation with chromosomal DNA in soil' and that 'their level of competence is influenced by their metabolic state' (Nielsen et al, 1997).…”
Section: Competence Of Acinetobacteris a Nutrient Boost Required?mentioning
confidence: 99%